Challenging Issues in the Implementation of Military Justice in Ukraine - Shkuropatskyi, O. I.; Andriiets, M. O. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article analyzes the conditions and reasons of the elimination of military courts, the issue of decision- making by courts of general jurisdiction in dealing with cases involving military personnel. The benefits of professional activity of military courts were mentioned. The conclusion about the necessity for recovery of military courts in Ukraine, taking into account the experience of foreign countries, regarding the place, structure and functioning of the military courts system, was made.